Does the Conservative Non-pharmacological Management of Knee Osteoarthritis in Switzerland Reflect the Clinical Guidelines? A Survey Among General Practitioners, Rheumatologists, and Orthopaedic Surgeons - Ettlin, Lea; Nast, Irina; Huber, Erika O.; Niedermann, Karin (Frontiers in Rehabilitation Sciences, 2021)
Introduction: International Guidelines recommend exercise, education and weight management (if appropriate) as the first-line conservative treatment for patients with knee osteoarthritis (OA) to enhance self-management of the patient. The aim of this study was to investigate the current conservative non-pharmacological management of patients with knee OA in Switzerland and to explore the perceived barriers and facilitators to the application of the guideline recommendations. Materials and Methods: Eleven semi-structured interviews with selected general practitioners (GPs), rheumatologists and orthopaedic surgeons were performed. Based on these results, an online survey was developed to send to the members of three scientific societies. Questions addressed the frequency of diagnostic measures, treatment options, reasons for referral to exercise, as well as barriers and facilitators. Results: A total of 234 members responded. They indicated that patients normally present due to pain (n=222, 98.2%) and functional limitations of the knee (n=151, 66.8%). In addition to clinical assessment, mostly X-ray (n=214, 95.5%) and MRI (n=70, 31.3%) were used as diagnostic measures. Treatment options mostly involved patient education for the diagnosis (n=223, 98.6%) and suitable activities (n=217, 96.0%), pharmacological treatment (n=203, 89.8%) and referral to physiotherapy (n=188, 83.2%). The participants estimated to have referred 54.0% of their knee OA patients for specific exercise. The referral to exercise was driven by the ‘patients’ expectation/high level of suffering’ (n=73, 37.1%), as well as by their ‘own clinical experience’ (n=49, 24.9%). The specialists rated the most important barriers to referral to exercise as ‘disinterest of patient’ (n=88, 46.3%) and ‘physically active patient’ (n=59, 31.1%). As the most important facilitators, they rated ‘importance to mention exercise despite the short time of consultation’ (n=170, 89.4%) and ‘insufficiently physically active patient’ (n=165, 86.9%). Discussion: A substantial evidence-performance gap in the management of patients with knee OA seems to exist in Switzerland. For the systematic referral to exercise as the first-line intervention, it may be helpful for the medical doctors to suggest a structured exercise programme to knee OA patients, rather than just advising general exercise.